Overcoming Resistance to Immunotherapy in Head and Neck Cancer Using Radiation: A Review - Hui, Caressa; Chau, Brittney; Gan, Greg; Stokes, William; Karam, Sana D.; Amini, Arya (Frontiers in Oncology, 2021)
Radiation therapy remains at the center of head and neck cancer treatment. With improvements in treatment delivery, radiation therapy has become an affective ablative modality for head and neck cancers. Immune checkpoint inhibitors are now also playing a more active role both in the locally advanced and metastatic setting and with improved systemic options, local noninvasive modalities including radiation therapy are playing a critical role in overcoming resistance in head and neck cancer. The aim of this review is to describe the role of radiation therapy in modulating the tumor microenvironment and how radiation dose, fractionation and treatment field can impact the immune system and potentially effect outcomes when combined with immunotherapy. The review will encompass several common scenarios where radiation is used to improve outcomes and overcome potential resistance that may develop with immunotherapy in head and neck squamous cell carcinoma (HNSCC), including upfront locally advanced disease receiving definitive radiation, recurrent disease undergoing re-irradiation, and the novel oligometastatic and oligoprogressive settings. Lastly, we will review the potential toxicities of combined therapy and future directions of their role in the management of HNSCC.